WAYS FOR A LEADER TO WORK ON SPEECH AND IMPROVE SPEAKING SKILLS - Suyunov Dilmurod Kholmuradovich; Kodirov Tuygun Uzokovich (American Journals, 2023)
The article analyzes issues such as the management process and the formation of the leader as a speaker, the history of the study of management as a theoretical science, the art of management, the influence of management, management psychology, social psychology, and the leader's social role in management.
Keywords: Leader, orator, Management, Art of management, social, Work, forces to think logically. Logical thinking, efficiency, Society, development.